A universal layer-by-layer solution-processing approach for efficient non-fullerene organic solar cells. Issue 1 (19th December 2018) - Sun, Rui; Guo, Jing; Sun, Chenkai; Wang, Tao; Luo, Zhenghui; Zhang, Zhuohan; Jiao, Xuechen; Tang, Weihua; Yang, Chuluo; Li, Yongfang; Min, Jie
Abstract : A universal layer-by-layer solution-processing approach is proven to be effective for the fabrication of high-performance non-fullerene organic solar cells. Abstract : Layer-by-layer (LbL) solution processing is a cost-effective technology for the large-scale fabrication of organic solar cells (OSCs). In this work, LbL OSCs were fabricated using PTQ10/J71 as donors and ITC6-IC/IDIC/MeIC/ITCPTC/ITIC as non-fullerene acceptors (NFAs) without using orthogonal solvents and appropriate co-solvents. Compared with traditional bulk heterojunction (BHJ) OSCs, the corresponding solution-processed LbL devices exhibited higher or comparable power conversion efficiencies (PCEs), which had the advantages of reduced energy loss, stronger absorption spectra, better vertical phase separation, partially increased charge transport property and charge collection efficiency. Furthermore, taking the J71/ITC6-IC and PTQ10/IDIC LbL systems as examples, we fabricated large-area LbL OSCs using the doctor-blading process, which is closer to the roll-to-roll (R2R) technology. Importantly, both OSCs based on J71/ITC6-IC and PTQ10/IDIC LbL with an active area of 1.00 cm 2 demonstrated encouraging PCEs of over 10%, which is the record efficiency for large-area LbL OSCs reported in the literature to date. Our work indicates that the solution-processed LbL approach not only presents good generality and high device performance, but also is a superior alternative to the BHJ method for the initial evaluation of photovoltaic materials and the industrial production of R2R OSCs.